TI_GERICHTE 17.2014.106 vom 2. Februar 2015 , Guida nonostante revoca della licenza di condurre (art. 95 cpv. 2 LCStr). Errore sull'illiceità (art. 21 CP) - TI Tribunale d'appello (2015)
Guida nonostante revoca della licenza di condurre (art. 95 cpv. 2 LCStr). Errore sull'illiceità (art. 21 CP)